Geophysical Researches of Portals Will Allow to Discover Invisible Universes and Explore Them - Antonov, Alexander Alexandrovich (European Journal of Applied Sciences, 2023)
The article proves that the version of the special theory of relativity (STR) presented in physics textbooks is incorrect. This is because in the early 20th century science lacked experimental knowledge required for the STR to be created, and the postulate (called the principle of light speed non-exceedance) that replaced the knowledge turned out to be incorrect and has been experimentally refuted in the 21st century. It is explained that tsunami and piano music would not exist, church bells would not ring and even swings would not swing on playgrounds, if the generally accepted version of the STR were true. Moreover, this version of the STR also implies that Ohm’s law as interpreted by Steinmetz used daily by millions of radio and electrical engineers in their practice does not exist, and therefore radio engineering and electrical engineering should not exist either. That is why, an alternative version of the STR has been created instead of the incorrect one. It follows from this that there is an invisible Multiverse whose universes are interconnected by numerous portals, including those located on Earth. And at least some of anomalous zones are entrances to portals. Geophysical exploration of portals is very necessary, as they will allow us to obtain new valuable knowledge about our Multiverse and confirm the correctness of the alternative version of STR.